Pengaruh Perspektif Diamond Fraud Terhadap Perilaku Kecurangan Akademik Dengan Meta AI Sebagai Variabel Moderasi - Savina Dina Saputri; Khresna Bayu Sangka (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to analyze the influence of the fraud diamond perspective, which consists of pressure, opportunity, rationalization, and capability, on academic cheating behavior with Meta AI as a moderating variable. The research was conducted on Economics subject students at SMA Negeri 2 Karanganyar using a descriptive quantitative approach. The population of this study consisted of 230 students who were selected simple random sampling. Data were collected through questionnaires, and the validity of the instruments was tested using the Pearson product-moment correlation, while the reliability was tested using Cronbach’s alpha. Data analysis techniques included descriptive statistical analysis, moderated regression analysis (MRA), and t-tests. The findings reveal that pressure, opportunity, rationalization, and capability each have a positive and significant influence on academic cheating behavior. However, the moderating role of Meta AI shows mixed results. Meta AI does not moderate the effect of pressure and capability on academic cheating behavior, while it moderates the effect of opportunity and rationalization on cheating behavior. These findings suggest that although Meta AI provides certain control in reducing rationalization and reinforcing the role of opportunity, it is not sufficient to reduce the effect of pressure and capability on academic dishonesty. Therefore, schools and educators need to strengthen ethical education and digital literacy to prevent the misuse of technology in academic contexts. Keywords: Fraud Diamond, Academic Cheating, Meta AI, Students, Economics